EFFECTIVE APPROACHES TO ENGLISH LANGUAGE INSTRUCTION FOR ELEMENTARY-LEVEL STUDENTS THROUGH HANDS-ON ACTIVITIES - Akbarov Alijon Ikrom ogli (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: Currently, the need to master a foreign language is dictated by the modern social order of society,which is due to the growth of intercultural contacts in all spheres of human activity. Learning a foreign language at school begins in the elementary grades, and from that moment the whole learning process acquires a communicative orientation. The methodology of teaching a foreign language in elementary school is still in the formative stage, today the search for effective methods of teaching a foreign language in junior school is actively carried out, which are based on the psychological characteristics of students of this stage. Information and communication technologies are widely used in the education system, as well as in other industries. Conducting classes with the use of new pedagogical technologies requires special intellectual abilities from the teacher. Education can be transformed only when the teacher can accurately identify the interests of students, correctly direct them to the path of achieving the goal. The teacher’s use of interactive methods in his classes contributes to the development of a real environment of rivalry and cooperation.